Ethnoveterinary Medicine and Ethnopharmacology in the Main Transhumance Areas of Castilla-La Mancha (Spain) - Rivera, Diego; Verde, Alonso; Fajardo Rodríguez, José; Ríos, Segundo; Alcaraz, Francisco; Cárceles, Carlos; Ortíz, Juana; Valdés, Arturo; Ruíz-Gallardo, Jose Reyes; García-Flores, Aida; Palazón, José Antonio; Obón, Concepción (Frontiers in Veterinary Science, 2022)
Ethnoveterinary is the systematic investigation and application of folk veterinary knowledge, theory and practice. A common theme in this field is ethnoveterinary pharmacology, the study of traditional remedies for different pathologies affecting domestic animals. In this study we document the ethnoveterinary and ethnopharmacology in the context of traditional transhumance routes that cross Castilla La Mancha from north to south. Transhumance, is to move from land to land. It is a type of grazing system that allows to take advantage of the winter pastures (wintering places) and summer pastures through the seasonal movement, twice a year, of the cattle and their shepherds. Our study is based on over 200 interviews (from 1994 to 2021) in 86 localities along eight major transhumance routes “cañadas reales” and 25 other minor transhumance ways and involved 210 informants, 89 single and 121 groups, involving 562 individuals, from which the majority were men. The 63 recorded pathologies and their treatments are discussed. 202 species and substances, belonging to 92 different families, have been recorded from the interviews, of which most are plants. Amid the toxic plant species, the most cited in the interviews are Erophaca baetica (L.) Boiss., Lupinus angustifolius L. and Oenanthe crocata L. Several among the species reported as toxic were reservoirs of pathogens or markers for dangerous areas. One of the fields most widely covered in our study is that of the prevention, protection and control of endo- and ectoparasites. This control is carried out mainly by means of aromatic plants. As a polyvalent species, Daphne gnidium L. is outstanding and contributes with one tenth of the records of our study. Among the species of fundamentally therapeutic use, Cistus ladanifer L. stands out by far. Principal Coordinate Analysis (PCoA) based on the repertories of ingredients, separates the routes whose most important sections run through siliceous terrain with its characteristic flora, especially in the provinces of Ciudad Real and Toledo, from the routes that run through the limestone terrain of Albacete and Cuenca, and link the Eastern Mancha and the “Serranía de Cuenca” with Andalusia and the Spanish Levant.